Integration of Mahalanobis-Taguchi system and time-driven activity-based costing in production environment - Filzah Lina, Mohd Safeiee (2023)
In the production environment, the process is considered stable when the assignable causes have been eliminated from the process and then, the process parameters are concluded significant to the output. By solely depending on the control chart to conclude the significant parameter is not well justified yet the degree of contribution is vague. Meanwhile, the costing structure in the production environment is mainly based on the consumed activities. Although the costing structure is appropriate, it does not provide an integrated view of enterprise-wide profitability opportunities and could not be easily updated to accommodate changing circumstances. There are a lot of frameworks related to system integration such as an approach of remaining useful life prediction based on risk assessment and degradation state coefficient into the Mahalanobis distance, and a cost model to take into consideration uncertainty and variability in the computation of product cost stochastically. It proves from the literature that a new study is needed to develop a new framework to integrate between the quality and cost for better product costing in the production environment. The main objective of this work is to integrate the MahalanobisTaguchi system (MTS) and time- driven activity-based costing (TDABC) in the production environment. The collection data is obtained from a company located in Kuantan, Pahang. MTS analyses the degree of contribution of parameters while TDABC analyses the capacity utilization in production environment. As a result of degree of contribution, healthy and unhealthy groups have been plotted in the scatter diagram to indicate the distance of rejected components to the accepted components. Fortunately, both groups are not identical and have positive correlation. In order to obtain lower Mahalanobis distance which closer tohealthy group, positive degree of contribution should be decreased while negative degree of contribution should be increased. As a result of capacity utilization, 3 clusters are found for capacity utilization such as Type I which is the workstation is over- utilized the provided apportionment, Type II which is the workstation utilized a small portion of provided apportionment and Type III which the workstation largely utilized the provided apportionment. Obviously, Type III is most prominent because the management always set the expenditure to achieve certain annual production. By knowing the unused capacity of time and cost, management also can forecast their resources and expenses in the future more accurately to reduce any wastes. As a result of frameworks of system integration, 4 types of integration are discussed such as Integration A (conventional-ABC), Integration B (conventional-TDABC), Integration C (MTS-ABC) and Integration D (MTS-TDABC). As a result of validation, Integration D is the best compared the others in the production environment because MTS considers degree of contribution for each parameter which influence to the increment or decrement to the final cost and the TDABC develops capacity cost rate from the related cost of capacity supplied and time equations with high flexibility to absorb the complexity of the product. Therefore, integration between MTS and TDABC means different degree of contributions of parameters will affect the time equations and capacity cost rate to produce better cost of product in production environment.